Changes in Oxidative Stability and Fatty Acid Composition of Commercially Produced Chips During Shelf-Life - DAGLIOGLU, ORHAN; TASAN, MURAT; GECGEL, UMIT; DAGLIOGLU, FIGEN (Asian Journal of Chemistry, 2010)
Changes in oxidative stability and fatty acid composition of commercially produced potato and corn chips during shelf-life were studied. The chips were stored at ambient conditions for four months which was given by the manufacturers. At definite time intervals, the absorbed oil was extracted from the chips and analyzed for free fatty acids, peroxide value, rancimat induction time and fatty acid composition. Sensory analysis for rancid flavour was carried out by an expert panelist group using a hedonic scale. Changes in fatty acid composition throughout shelf-life of potato and corn chips were insignificant (p > 0.05). Even though significant differences were determined in free fatty acids, peroxide value and induction time values as well as sensory scores (p < 0.05), potato and corn chips maintained their oxidative and hydrolytic stability and rancid flavour was sensorial acceptable at the end of shelf-life.